Social Skills and Behavior Problems and Relation between them in Early Childhood in the Hashemite Kingdom of Jordan - Amal Al-Khatib (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
There is a lack of research on social skills and behavior problems among young children in Jordan. Therefore, the present study explored Jordanian parents' perceptions of the social skills and behavior problems of their kindergarten children. The study also attempted to find the extent to which social skills are related to behavior problems. Data was collected from a convenience sample 131 Jordanian parents of children attending private kindergartens in Amman using a two-part questionnaire. The first part consisted of 40 items across four domains (cooperation, assertion, responsibility, and self-control). The results showed that parents reported that, their children, overall, exhibited above average social skills. None of the items in the four domains were rated below average by parents. Parents' ratings of their children's cooperation and assertion skills were higher than their ratings of their children's responsibility and self-control skills. The results also showed that parents perceived their children to have a moderate level of externalized behavior problems and a low level of internalized behavior problems. Finally, the results indicated a negative significant correlation between social problems and behavior problems. The limitations and implications of these findings were discussed.